2018
DOI: 10.1097/paf.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Sampling Site on Postmortem Cerebrospinal Fluid Biochemistry

Abstract: Cerebrospinal fluid (CSF) is often analyzed at postmortem. The presented preliminary study compared postmortem CSF samples for biochemical analysis from the subarachnoid space around the spinal cord and ventricular space of the brain. This study compared 15 paired CSF samples in which the CSF from the subarachnoid space via lumbar puncture had higher sodium and chloride levels and lower magnesium and potassium levels than CSF from the ventricles. The differences correlated significantly with the deceased's age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A significant rostro-caudal concentration gradient has also been shown for tryptophan, HVA, 5-HT and 5-HIAA [33,58,59]. A recent study showed statistical differences in electrolytes in CSF between the lumbar and the ventricular sites, with the post-mortem samples obtained from the ventricular subarachnoid space having statistically lower sodium and chloride but higher magnesium and potassium [60]. Because of divergent gradients of diffusion, the values obtained from these different sites should not be compared with one another.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
See 1 more Smart Citation
“…A significant rostro-caudal concentration gradient has also been shown for tryptophan, HVA, 5-HT and 5-HIAA [33,58,59]. A recent study showed statistical differences in electrolytes in CSF between the lumbar and the ventricular sites, with the post-mortem samples obtained from the ventricular subarachnoid space having statistically lower sodium and chloride but higher magnesium and potassium [60]. Because of divergent gradients of diffusion, the values obtained from these different sites should not be compared with one another.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…It is assumed that the intracranial fluid would better reflect the subtle biochemical changes occurring in the brain compared to the spinal fluid [27,60].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The above observations are significant since cerebrospinal fluid collected from the ventricular system of the brain differs in biochemical composition from that collected from the spinal cord. Both of these anatomical locations cannot be treated equally until more data is collected [ 15 ]. Fluid from the ventricular system has one significant disadvantage—it is not sufficiently isolated and therefore undergoes greater post-mortem changes than fluid collected from the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebrospinal fluid in the subarachnoid space around the spinal column may be more stagnant owing to gravitational effects, whereas in the ventricles, CSF may have a higher cellular turnover. The brain is a highly cellular and metabolically active organ [ 15 ]. Brain tissue decomposes and putrefies right after death.…”
Section: Introductionmentioning
confidence: 99%